Analysis of the impact of massage, physiotherapy, and nutrision provision of recommended dietary allowances on the confidence of road race cycling athlete - Darni Darni; Deri Putra; Hendri Neldi; Deswandi Deswandi; Hilmainur Syampurma; Ade Zalindro (Jorpres (Jurnal Olahraga Prestasi), 2023)
The purpose of this study is to analyze the effect of massage, physiotherapy, and nutrision provision of recommended dietary allowances on the confidence of road race cycling athletes. This study's design employs a mixed methods approach, specifically a qualitative approach with a case study method and a quantitative one with an ex post facto method. The subject in this study included ten athletes who received massage, physiotherapy and recommended dietary allowances. Measurement of athlete self-confidence improvement following data collection via survey, massage, physiotherapy, and nutrition administration, followed by interviews with athletes. The data came from the results of in-depth interviews with individuals, specifically between interviewers and research respondents. In this study, researchers used a semi-structured interview method. This research analysis technique goes through the process of data reduction, data display, and verification. Data processing techniques use coding, data classification, categorization, analyzing units of meaning in categories, looking for relationships between categories, and making reports where the results of the analysis are suppressed in the form of draft research reports.The result of this study shows that the provision of massage manipulation has a confident effect on road race cycling athletes. Before being given a massage the athlete feels stiffness in the muscles and after being given the massage the athlete feels fitter. Physiotherapy can increase athletes' confidence through Exercise therapy and Thermotherapy (Heat therapy).  Providing nutritional needs based on recommended dietary allowances increases the confidence of Road Race Cycling Athletes